Caracterização de três testes funcionais do membro superior : contribuições da eletromiografia para a terapia ocupacional - Silva, Natália Sanches (Universidade Federal de São Carlos, 2016)
Introduction: when any part of the Upper Limb (UL) is injured, the demands brought by customers are assessed from different instruments, however studies show that there is no consensus on an ideal instrument for assessing the quantity and quality of the UL function, demonstrating the need to find tools that can provide precise measurements of how the UL perform tasks. Objectives: characterize the Box and Block Test (BBT), the Functional Dexterity Test (FDT) and the Nine Hole Peg Test (NHPT) regarding the electromyographic activity of the trapezius upper fibers muscle (TUF), deltoid anterior fibers muscle (DAF) and posterior fibers (DPF), the pectoralis major muscle (PM), the biceps (BB) and triceps brachii (TB), extensor carpi radialis brevis (ERB) and flexor digitorum superficialis (FDS) and verify if there are differences in muscle activation during the three tests between genders. Method: non-experimental research, descriptive transversal quantitative approach. Were selected 20 college students of both genders, average age of 24 years and average Body Mass Index (BMI) of 24 kg m-2. Data analysis was made using MiotecSuite 1.0 software and by Friedman, Dunn, Mann-Whitney and Spearman statistical tests. Results: For the three tests, the TUF was the most activated, followed by FDS. DAF, DPF and PM showed a high percentage of neuroactivation in BBT test. ERB showed percentage of activation between intermediate and high in FDT and NHPT tests. Conclusion: FDT and NHPT tests may be more recommended to assess the function of the UL of persons with upper extremity lesions, while the BBT may be indicated for both proximal and distal lesions of UL. Women have a higher muscle activation than men, and this fact can be justified by the muscular genetic difference between them.
Keywords: Terapia Ocupacional; Membros Superiores; Avaliação Funcional; Testes Funcionais Padronizado; Eletromiografia; Occupational Therapy; Upper Limbs; Functional Assessment; Standardized Functional Tests; Electromyography; CIENCIAS BIOLOGICAS